Pesantren Sebagai Bentuk Identitas Pendidikan Islam - Mahrus Mahrus (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2017)
Pesantren is one of Islamic Education Institutions (IEIs) that dominant and concern on teaching religion then have impact on islamic culture, tradition and doctrine. Pesantren also have a role in the formation of civilization of the nation. Today, Pesantren has to to prepare facing globalization challenge and generate competitive graduates in this globalization era. For that, pesantren has to be able to be a global insightful institution and having excellence human resources, especially in Islamic education. Therefore, it is need minset transformation towards keep pace with changing, that oriented on generate graduates with three competencies: (1) competency to survive; (2) competency to enhance their quality of life; (3) competency to progress and adapt with an-ever changing era.